The effect of the rehabilitative approach in the case of a replacing pelvic joint for men in age (70-75) years 1D. Basil Abdel satar, 2D. Ali Talal Abdoallh - satar, D. Basil Abdel; D. Ali Talal Abdoallh (International Journal of Psychosocial Rehabilitation, 2020)
Elderly people usually expose to multiple health problems, some of them caused by Physical and functional weakness as a result from aging and demolition operation especially in the structural system where the bones start with weakness because of the intense Osteoporosis which make bones easy to break and need a long process of care and treatment from where nutrition and rehabilitative effort in order to recover gradually. We may find that a large percentage of bone fracture cases that the elderly expose to are in the pelvic region, especially, the head of the thigh that is exposed to types of fractures as a result of falling on the pelvic and loss control on the body from the weakness of the surrounding muscles, which is necessary require surgical intervention for patient and control the condition based on the health condition of the patient, Therefore, the post-operative stage has a major role in restoring the patient’s ability to return again to practice life closer to normal through the appropriate rehabilitation effort for the patient’s condition.